2002
DOI: 10.1093/carcin/23.9.1491
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent and adult soy intake and risk of breast cancer in Asian-Americans

Abstract: The association between soyfood intake and breast cancer risk is controversial. Most of the epidemiologic studies published on this topic in the 1990s were not designed to specifically address this question. We conducted a population-based, case-control study of breast cancer among Chinese, Japanese and Filipino women in Los Angeles County to further investigate the role of soy. Our primary objective was to quantify breast cancer risks associated with intake of soy during adolescence and adult life among Asian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
289
3
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 374 publications
(316 citation statements)
references
References 27 publications
18
289
3
6
Order By: Relevance
“…Among such external factors, diet is thought to play an important role. A low incidence of breast cancer in Asia has been attributed in part to a high intake of flavonoids [22,23]. The incidence of cancer increases when Asian women move to the United States, where the average diet is rich in fat and confers a strong significant protective effect during adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Among such external factors, diet is thought to play an important role. A low incidence of breast cancer in Asia has been attributed in part to a high intake of flavonoids [22,23]. The incidence of cancer increases when Asian women move to the United States, where the average diet is rich in fat and confers a strong significant protective effect during adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Age at first pregnancy was not included in the baseline model since there was no significant improvement in the fit of the regression model with this variable. We considered additional lifestyle factors, including smoking habits; intake of alcohol, coffee, soy and dark leafy greens; family history of cancer; and physical activity, as they were found to be associated with tea consumption in this study (Table I) and in some previous studies or emerged as significant risk factors in this population 12,16 (referred as model B adjusted ORs in Table II 12,16 cases and controls were similar in terms of birthplace, education, age at menarche and body size but cases were significantly more likely to be nulliparous, had fewer live births, had lower consumption of soy and were less physically active than controls (data not shown). Table I shows the age-adjusted mean daily intake of black and green tea separately and the 2 teas combined by demographic and various lifestyle factors.…”
Section: Methodsmentioning
confidence: 99%
“…According to experimental (Lamartiniere et al, 1995;Murrill et al, 1996;Hilakivi-Clarke et al, 1999) and epidemiological studies (Shu et al, 2001;Wu et al, 2002), the timing of soy exposure during developmental years may be crucial for the protective effects from soy. In animals, prepubertal exposure to soy appears to be more effective than adult exposure in reducing mammary tumor formation (Lamartiniere et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In animals, prepubertal exposure to soy appears to be more effective than adult exposure in reducing mammary tumor formation (Lamartiniere et al, 2002). Furthermore, two case-control studies revealed that women with high soy intake during adolescence had half the risk of breast cancer as compared to those who consumed fewer soy foods (Shu et al, 2001;Wu et al, 2002). Thus, regular soy consumption during childhood and adolescence may lower the risk for breast cancer later in life.…”
Section: Introductionmentioning
confidence: 99%